Implication of nano-antioxidant therapy for treatment of hepatocellular carcinoma using PLGA nanoparticles of rutin. (22nd March 2018) - Pandey, Preeti; Rahman, Mahfoozur; Bhatt, Prakash Chandra; Beg, Sarwar; Paul, Basudev; Hafeez, Abdul; Al-Abbasi, Fahad A; Nadeem, Muhammad Shahid; Baothman, Othman; Anwar, Firoz; Kumar, Vikas
Aim: The present work describes the development of poly(lactic co-glycolic acid) (PLGA) nanoparticles (NPs) of rutin (RT) for the treatment of hepatocellular carcinoma in rats.Materials & methods: RT-loaded PLGA NPs (RT-PLGA-NPs) were prepared by double emulsion evaporation method. Further these are optimized by Box–Behnken design. PLGA NPs were evaluated for size, polydispersity index, drug-loading capacity, entrapment, gastric stability, in vitro drug release, in vivo preclinical studies and biochemical studies.Results: Preclinical evaluation of RT-PLGA-NPs for anticancer activity through oral route exhibited significant improvement in hepatic, hematologic and renal biochemical parameters. Highly superior activity was observed in regulating oxidative stress and inflammatory markers, antioxidant enzymes, cytokines and inflammatory mediators and their role on plasma membrane ATPases responsible for destruction in liver tissues.Conclusion: Histopathological evaluation indicated reduced incidence of hepatic nodules, necrosis formation, infiltration of inflammatory cells, blood vessel inflammation and cell swelling with RT-PLGA-NP treatment along with considerable downregulation in the levels of proinflammatory cytokines.